Factors influencing birth weight among pregnant mothers in Sarikei, Sarawak, 1994 - Osman Rafaie,; Hanafiah Mohd Salleh, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
The purpose of this cross sectional study was to study the influences of biological factors, health and socioeconomic status as well as antenatal care on birth weight in Sarikei Division, Sarawak. Two hundred and twenty seven singleton postnatal mothers who delivered at Sarikei Hospital, Sarawak from 21 December 1993 to 21 February 1994 were selected for the study. The approach used in this study differed from previous studies since the data was collected directly from the postnatal mothers and their newborns and not only passed medical records. Using guided questionnaires the data was collected by interviewing the postnatal mothers as well as referring to the antenatal cards and case notes. Birth weight was taken within half an hour after delivery. It was found that the prevalence of low birth weight in Sarikei Division , Sarawak is 10.2% .The study found that the factors that influenced birth weight were maternal age, maternal height, ethnic group, gravida, parity, family income, maternal education, bad obstetric history, chronic illness, number of antenatal visit, gestational age and sex of the newborn .